Enhancing therapeutic antibody profiling: orthogonal strategies for stability and quality assessment - Metzendorf, Nicole G.; Petersen, Inga; Hultqvist, Greta (Frontiers in Pharmacology, 2025)
Today, a variety of multivalent antibody formats can be engineered, offering significant flexibility for therapeutic and diagnostic approaches. While unmodified antibodies have evolved to be structurally stable, extensive engineering, such as domain fusion or size reduction, can compromise their thermal stability, conformational integrity, and overall functional performance. As a result, reliable antibody development requires rigorous biophysical characterization to ensure protein quality, including assessments of purity, folding, stability and aggregation propensity. In this study, we systematically evaluate a panel of analytical methods, including SDS-PAGE, nano differential scanning fluorimetry (nanoDSF), dynamic light scattering (DLS), size exclusion chromatography (SEC), mass photometry, circular dichroism (CD), small-angle X-ray scattering (SAXS) and electron microscopy, to characterize a series of antibody-derived constructs. These include a full-length IgG (Ab1), a bivalent fusion antibody (Ab1-scFv1), a bispecific tandem single-chain fragment variable (bi-scFv2-scFv1) and single-chain variable fragments (scFv1, scFv3, and scFv4). These constructs served as representative model proteins to assess method performance and sensitivity to structural and biophysical differences. Our results show that full-length antibodies (Ab1 and Ab1-scFv1) exhibit high thermal and structural stability and remain predominantly monomeric across all tested conditions. In contrast, engineered fragments, particularly bi-scFv2-scFv1 and scFv variants, display increased aggregation propensity and reduced conformational stability, as evidenced by higher polydispersity in DLS, early elution peaks in SEC, and altered thermal folding profiles in nanoDSF. SAXS and CD further revealed extended, flexible conformations in larger constructs and partial folding deficiencies in smaller fragments. Overall, this study underscores the importance of integrating orthogonal analytical methods to ensure a robust evaluation of antibody format stability and integrity. With the increasing complexity of engineered antibody therapeutics, these tools offer practical insights into selecting appropriate constructs for downstream development, enhancing experimental reproducibility, and mitigating risk in early-stage research and therapeutic design. Furthermore, many of the assessed quality attributes, such as monodispersity, conformational stability, and aggregation behaviour, are directly relevant to in vivo performances, including pharmacokinetics and immunogenicity making such characterization essential for advancing antibody candidates toward clinical applications.